2021
DOI: 10.1136/bmjresp-2020-000866
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and risk of respiratory infection among adults: evidence from the multiethnic study of atherosclerosis (MESA)

Abstract: BackgroundAir pollution may affect the risk of respiratory infection, though research has focused on uncommon infections or infections in children. Whether ambient air pollutants increase the risk of common acute respiratory infections among adults is uncertain, yet this may help understand whether pollutants influence spread of pandemic respiratory infections like COVID-19.ObjectiveTo estimate the association between ambient air pollutant exposures and respiratory infections in adults.MethodsDuring five study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Their results support our findings and point to the existence of an independent effect of NO 2 exposure on SARS-CoV-2 mortality. This conclusion is in line with a number of previous evidence demonstrating clear relationships between NO 2 exposure, lung inflammation and functional abnormalities (Jiang et al 2019;Johannson et al 2014;Sack et al 2017), vulnerability to respiratory infections (Kirwa et al 2021), lymphopenia, and reduced amount of lymphocyte subsets (Frampton et al 2002;Sandstrom et al 1992;Solomon et al 2000;Steenhof et al 2014). Human studies showed that exposure to NO 2 is able to induce acute exacerbation of idiopathic pulmonary fibrosis (Johannson et al 2014), to increase interstitial lung abnormality (Sack et al 2017), to promote respiratory inflammation, and to affect lung function acting by epigenetic mechanisms (i.e., hypomethylation of the arginase − nitric oxide synthase pathway) (Jiang et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Their results support our findings and point to the existence of an independent effect of NO 2 exposure on SARS-CoV-2 mortality. This conclusion is in line with a number of previous evidence demonstrating clear relationships between NO 2 exposure, lung inflammation and functional abnormalities (Jiang et al 2019;Johannson et al 2014;Sack et al 2017), vulnerability to respiratory infections (Kirwa et al 2021), lymphopenia, and reduced amount of lymphocyte subsets (Frampton et al 2002;Sandstrom et al 1992;Solomon et al 2000;Steenhof et al 2014). Human studies showed that exposure to NO 2 is able to induce acute exacerbation of idiopathic pulmonary fibrosis (Johannson et al 2014), to increase interstitial lung abnormality (Sack et al 2017), to promote respiratory inflammation, and to affect lung function acting by epigenetic mechanisms (i.e., hypomethylation of the arginase − nitric oxide synthase pathway) (Jiang et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In a large cohort of adults explored over 12 years (multiethnic study of atherosclerosis, MESA), an increase in residential concentration of NO 2 from the 25th to the 75th percentile in the previous 2-6 weeks period was linked with 21% higher risk of reporting a recent respiratory infection (Kirwa et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that higher air pollution levels can significantly increase risk of respiratory infections in general. A study of 6814 multi-ethnic adults aged 44 to 84 years in 6 US cities reported that an increase of estimated PM 2.5 and NO x from 25 to 75% percentile increased the risk of respiratory infections by 1.04 (OR 1.04, 95% CI 1.00 to 1.09) and 1.15 (OR 1.15, 95% CI 1.10 to 1.20), respectively (Kirwa et al 2021 ). A Chinese study reported that increased outdoor levels of PM 2.5 , PM 10 , CO, and SO 2 were associated with significantly higher levels of influenza-like illness in both children and adults (Su et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although this should not be ruled out, as mentioned, air quality indicators also tend to proxy poor pulmonary health, which may increase death and case reporting, that is people with lung problems induced by air pollution are more likely to have symptomatic infections. It is well documented that long term exposure to certain pollutants has knock-on effects for people suffering from pulmonary viral infections [62][63][64][65]. For example, a study by Soukup et al [66] found that regulated inflammatory responses to viral infections are altered by exposure to PM10, potentially increasing the spread of infection and therefore increasing viral pneumonia-related hospital admissions.…”
Section: Environmental Factorsmentioning
confidence: 99%